2022
DOI: 10.3389/fmicb.2022.905901
|View full text |Cite
|
Sign up to set email alerts
|

Changes to the Gut Microbiome in Young Children Showing Early Behavioral Signs of Autism

Abstract: The human gut microbiome has increasingly been associated with autism spectrum disorder (ASD), which is a neurological developmental disorder, characterized by impairments to social interaction. The ability of the gut microbiota to signal across the gut-brain-microbiota axis with metabolites, including short-chain fatty acids, impacts brain health and has been identified to play a role in the gastrointestinal and developmental symptoms affecting autistic children. The fecal microbiome of older children with AS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 77 publications
(100 reference statements)
0
3
0
Order By: Relevance
“…Children with autism mainly exhibit psychoneurological symptoms, and gastrointestinal dysfunction and immune imbalance are prevalent in these studies, suggesting that the microbiome is involved in ASD (Adams et al, 2011;Lai et al, 2014;Petra et al, 2015;Madra et al, 2020). Numerous studies have investigated the microbiomes and metabolomes of children with autism compared with TD control groups (Coretti et al, 2018;Kang et al, 2018;Jones et al, 2022). In addition, animal experiments have confirmed that treatment with fecal microbiota from children with autism promotes behavior in mice associated with the core behavioral characteristics of ASD (Sharon et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Children with autism mainly exhibit psychoneurological symptoms, and gastrointestinal dysfunction and immune imbalance are prevalent in these studies, suggesting that the microbiome is involved in ASD (Adams et al, 2011;Lai et al, 2014;Petra et al, 2015;Madra et al, 2020). Numerous studies have investigated the microbiomes and metabolomes of children with autism compared with TD control groups (Coretti et al, 2018;Kang et al, 2018;Jones et al, 2022). In addition, animal experiments have confirmed that treatment with fecal microbiota from children with autism promotes behavior in mice associated with the core behavioral characteristics of ASD (Sharon et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Alteration in gut microbiome represents a promising strategy for the prevention and treatment of Alzheimer's as it aids in the reduction of inflammation, oxidative stress, amyloid or tau aggregation and repairs neurogenesis, blood brain barrier integrity, and improved behavioural and cognitive functions (Tarawneh & Penhos, 2022). Several articles published that discussed the role of gut microbiomes in Alzheimer's (Escobar et al, 2022; Kowalski & Mulak, 2019; Mulak, 2021; Solanki et al, 2023; Tarawneh & Penhos, 2022; van Olst et al, 2021), Parkinson's (Boertien, Murtomäki, et al, 2022a; Boertien, Murtomäki, et al, 2022b; Boertien, Pereira, et al, 2022; Hashish & Salama, 2023; Heinzel et al, 2021; Weis et al, 2021) and ASD (Iglesias‐Vázquez et al, 2020; Jendraszak et al, 2021; Jones et al, 2022; Wong et al, 2022; Zuffa et al, 2023) have been published over the past 10 years. However, AI based research founds deficit in this direction and still needs exploration.…”
Section: A Comparison Of Biomarkers Available For Non‐ml Based Techni...mentioning
confidence: 99%
“…Studies have reported that about 9%–91% of individuals with ASD have gastrointestinal symptoms ( Leader et al, 2022 ) and that prominent dysbiosis is observed in the gut microbiome of children with ASD ( Pulikkan et al, 2018 ; Jones et al, 2022 ). Meanwhile, the symptoms of individuals with ASD can be improved by regulating gut microbiota via fecal microbiota transplantation ( Kang et al, 2017 ) or probiotics supplements ( Shaaban et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%